Prevalensi, Profil, dan Outcome Koinfeksi Tuberkulosis-Human Immunodeficiency Virus di Salah Satu Rumah Sakit Rujukan Surakarta - Aliya Ully Nihaya; Zakky Cholisoh (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Tuberculosis (TB) and Human Immunodeficiency Virus (HIV) remain significant global health problems. Indonesia has one of the highest tuberculosis case burdens in the world and continues to experience an increasing number of HIV cases each year. TB-HIV coinfection has a significant negative impact on the immune system and patient treatment outcomes. Objective: This study aimed to assess the prevalence, sociodemographic and clinical profiles, and treatment outcomes of patients with TB-HIV coinfection at a referral hospital in Surakarta. Methods: This was a retrospective observational study with a descriptive approach conducted at a referral hospital in Surakarta from January to December 2024. Data were obtained from medical records of outpatients with TB-HIV coinfection who met the inclusion criteria (TB patients aged >18 years who were confirmed HIV-positive). Variables analyzed included sociodemographic characteristics (age, gender, area of residence, occupation), CD4 cell count, body weight, and treatment outcomes. Data analysis was performed descriptively using frequency distributions and percentages. Results: From 325 HIV patient medical records, 61 patients with TB-HIV coinfection were identified, yielding a prevalence of 18.77%. The highest proportion was found in the 41–50 years age group (26.20%), males (68.90%), and patients who were employed (82.00%). Most patients resided in rural areas (57.20%). Among 22 patients with complete CD4 data, 15 patients (24.60%) had CD4 counts ≥300 cells/mm³ and 7 patients (11.50%) had CD4 counts <300 cells/mm³. The mean body weight of patients was 53.84 kg. Treatment outcomes showed a cure rate of 37.70%, while suboptimal outcomes consisted of loss to follow up (29.50%), death (8.20%), treatment failure (8.20%), relapse (8.20%), and patients referred out (3.30%). Conclusion: The prevalence of TB-HIV coinfection at the referral hospital in Surakarta was 18.77%, with patient characteristics predominantly consisting of working-age males. The treatment success rate remains low (37.70%), falling below the WHO target (>85%). TB-HIV coinfection requires serious attention, and HIV screening among TB patients should be prioritized to facilitate early diagnosis and improve treatment outcomes for both diseases.